Modified mRNA Formulation and Stability for Cardiac and Skeletal Muscle Delivery - Magdalena M. Żak; Keerat Kaur; Jimeen Yoo; Ann Anu Kurian; Matthew Adjmi; Gayatri Mainkar; Seonghun Yoon; Lior Zangi (MDPI AG, 2023)
Directly injecting naked or lipid nanoparticle (LNP)-encapsulated modified mRNA (modRNA) allows rapid and efficient protein expression. This non-viral technology has been used successfully in modRNA vaccines against SARS-CoV-2. The main challenges in using modRNA vaccines were the initial requirement for an ultra-cold storage to preserve their integrity and concerns regarding unwanted side effects from this new technology. Here, we showed that naked modRNA maintains its integrity when stored up to 7 days at 4 °C, and LNP-encapsulated modRNA for up to 7 days at room temperature. Naked modRNA is predominantly expressed at the site of injection when delivered into cardiac or skeletal muscle. In comparison, LNP-encapsulated modRNA granted superior protein expression but also additional protein expression beyond the cardiac or skeletal muscle injection site. To overcome this challenge, we developed a skeletal-muscle-specific modRNA translation system (skeletal muscle SMRTs) for LNP-encapsulated modRNA. This system allows controlled protein translation predominantly at the site of injection to prevent potentially detrimental leakage and expression in major organs. Our study revealed the potential of the SMRTs platform for controlled expression of mRNA payload delivered intramuscularly. To conclude, our SMRTs platform for LNP-encapsulated modRNA can provide safe, stable, efficient and targeted gene expression at the site of injection.